2011
DOI: 10.1177/1076029611427900
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Abnormalities in Cirrhosis and Tumor-Related Portal Vein Thrombosis

Abstract: In order to investigate the relationship between hemostatic abnormalities and portal vein thrombosis (PVT) in hepatocellular carcinoma (HCC), platelets, prothrombin time (PT), activated partial thromboplastin time (aPTT), thrombin time, fibrinogen, d-dimer, fibrinogen degradation products (FDPs), protein C, protein S, antithrombin, plasminogen, antiplasmin, coagulation factors (CFs) V, VII, VIII, IX, XI, and XIII, von Willebrand factor (vWF), prothrombin fragment 1 + 2 (PF 1 + 2), tissue-type plasminogen activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Pancreatic carcinomas frequently invade or metastasize the liver. In a study done by Alkim H et al, it was shown that abnormalities of coagulation and fibrinolysis systems have some role in provoking thrombosis of portal veins in HCC (Alkim et al, 2012). There is no study suggesting this finding regarding pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic carcinomas frequently invade or metastasize the liver. In a study done by Alkim H et al, it was shown that abnormalities of coagulation and fibrinolysis systems have some role in provoking thrombosis of portal veins in HCC (Alkim et al, 2012). There is no study suggesting this finding regarding pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because cirrhosis leads to hypersplenism with a low platelet count, and as portal blood flow to the liver slows, formation of MVI is facilitated. Studies 22 have suggested that an increased serum level of von Willebrand factor and decreased levels of anticoagulants (especially antithrombin) in patients with cirrhosis played a significant role in provoking thrombosis and vascular invasion. In addition, a typical dynamic pattern of HCC suggested that there was sufficient tumor blood supply and good vascular connection between tumor vessels and branches of portal venous system, which facilitates cancer cell invasion and MVI formation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Therefore, they are a good indicator of its evaluation. 32,33 In this sense, the high levels of protein C in PAF could be interpreted as indicative of enhanced liver function and, respectively, enhanced protein C biosynthesis and secretion in the early hours of the rhythm disorder. The formation of ''pure'' groups in terms of comorbidities and medications affecting hemostasis is an important prerequisite for this claim (see Table 1).…”
Section: Discussionmentioning
confidence: 99%